Investigation of the effects of some demographic characteristics of female athletes on emotional intelligence and life satisfaction - Yücel, Ali Serdar; Korkmaz, Murat; Bal, Fatih; Özpınar, Saliha; Yaman, Çetin; Hergüner, Gülten; Kuyucu, Mihalis Michael (Sportis (A Coruña), 2024)
In many subjects and fields, emotional intelligence refers to the ability of individuals to understand, express and manage their own emotions and the emotions of others. Especially sport is known to have a significant effect on emotional intelligence. In this study, it was aimed to examine the effects of some demographic characteristics of female athletes on emotional intelligence and life satisfaction.  The participants were all women and analyses were performed by taking into account age groups, sports branches and education departments. Emotional intelligence and life satisfaction scales were evaluated by factor analysis and the suitability of the data was confirmed by Bartlett's test. The internal consistency of the questionnaire was evaluated with Cronbach's alpha coefficients. Anova, Kruskal Wallis and Jonckheere-Terpstra tests were used to analyse the data. All analyses were performed with SPSS v22.0. 34% of the participants were 18-21 years old, 45% were 22-25 years old and 21% were over 26 years old. 31% were interested in team sports and 69% were interested in individual sports. The fields of education are 37% coaching, 32% physical education and sports teaching, 31% sports management. According to the factor analysis results, Bartlett's test p<0.001 and KMO coefficient 0.896 were found. Cronbach's alpha coefficients ranged between 0.583 and 0.924. While some factors differed according to age, no difference was found according to sport branch. While evaluation of own emotions and social skills differed according to departments, other factors did not differ. Participants over 26 years of age had low scores in the use of emotions and life satisfaction factors. These findings provide important clues for developing strategies for improving emotional intelligence and increasing life satisfaction.